A critical account of intra -and inter- organizational knowledge management: Diversity, relationship making, and paradoxes - CHANG, Ya-Feng (Turkish Economic Review, 2017)
Abstract. Knowledge and networks (i.e., inter-organizational relationships) are two full conditions for successful intellectual capital management and organizational success. However, when researching related issue that fall into the domain area, people tend to follow more pragmatism and few would spend page space for more critical account of the nature of the issues examined. This article tried to revisit knowledge management in intra- and inter-organizational networked contexts and offer some critical insights that might stimulate more thinking in research and practices. Mainly, this article suggests thoughts on diversity, relationship making, and resolving paradoxical knowledge challenges. Keywords. Organization memory, Knowledge bases, Known memory. JEL. D80, L22, L23.